Task-shifting point-of-care CD4+ testing to lay health workers in HIV care and treatment services in Namibia - Francina Kaindjee-Tjituka; Souleymane Sawadogo; Graham Mutandi; Andrew D. Maher; Natanael Salomo; Claudia Mbapaha; Marytha Neo; Anita Beukes; Justice Gweshe; Alexinah Muadinohamba; David W. Lowrance (AOSIS, 2017)
Introduction: Access to CD4+ testing remains a common barrier to early initiation of antiretroviral therapy among persons living with HIV/AIDS in low- and middle-income countries. The feasibility of task-shifting of point-of-care (POC) CD4+ testing to lay health workers in Namibia has not been evaluated. Methods: From July to August 2011, Pima CD4+ analysers were used to improve access to CD4+ testing at 10 selected public health facilities in Namibia. POC Pima CD4+ testing was performed by nurses or lay health workers. Venous blood samples were collected from 10% of patients and sent to centralised laboratories for CD4+ testing with standard methods. Outcomes for POC Pima CD4+ testing and patient receipt of results were compared between nurses and lay health workers and between the POC method and standard laboratory CD4+ testing methods. Results: Overall, 1429 patients received a Pima CD4+ test; 500 (35.0%) tests were performed by nurses and 929 (65.0%) were performed by lay health workers. When Pima CD4+ testing was performed by a nurse or a lay health worker, 93.2% and 95.2% of results were valid (p = 0.1); 95.6% and 98.1% of results were received by the patient (p = 0.007); 96.2% and 94.0% of results were received by the patient on the same day (p = 0.08). Overall, 97.2% of Pima CD4+ results were received by patients, compared to 55.4% of standard laboratory CD4+ results (p < 0.001). Conclusions: POC CD4+ testing was feasible and effective when task-shifted to lay health workers. Rollout of POC CD4+ testing via task-shifting can improve access to CD4+ testing and retention in care between HIV diagnosis and antiretroviral therapy initiation in low- and middle-income countries.